2022
DOI: 10.1186/s12974-022-02580-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, therapeutic strategies and biomarker development based on “omics” analysis related to microglia in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease and the most common cause of dementia. Among various pathophysiological aspects, microglia are considered to play important roles in the pathogenesis of AD. Genome wide association studies (GWAS) showed that the majority of AD risk genes are highly or exclusively expressed in microglia, underscoring the critical roles of microglia in AD pathogenesis. Recently, omics technologies have greatly advanced our knowledge of microglia biology in AD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 194 publications
(304 reference statements)
0
11
0
Order By: Relevance
“…Yan et al (2023) showed that Icariin treatment significantly reduced tau hyperphosphorylation at the Thr217, Ser199/202, Thr231, and Ser396/404 sites in AD mice. The pathophysiology of AD involves not only the accumulation of aberrant protein aggregates but also neuroinflammation ( Gao et al, 2022 ). Glial cells are the primary immune cells in the brain and exert beneficial and neuroprotective effects by removing pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Yan et al (2023) showed that Icariin treatment significantly reduced tau hyperphosphorylation at the Thr217, Ser199/202, Thr231, and Ser396/404 sites in AD mice. The pathophysiology of AD involves not only the accumulation of aberrant protein aggregates but also neuroinflammation ( Gao et al, 2022 ). Glial cells are the primary immune cells in the brain and exert beneficial and neuroprotective effects by removing pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…However, considering the fact that we also included amyloid negative MCI cases in our study that might contain different underlying pathologies, future studies should confirm our results in larger MCI amyloid positive and negative groups. Furthermore, it could be interesting to further explore how a panel of these markers would be informative for monitoring the response of anti-inflammatory drugs [ 14 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of microglia function in AD is complex and is dependent on many factors including activation state and disease stage. For example, it has been proposed that moderately activated microglia are neuroprotective in the early stages of AD, while chronically activated microglia may be detrimental in later stages (reviewed in [ 64 66 ]). Genetic AD risk factors and sex may also impact the extent that microglia are beneficial, neutral, or detrimental for cognitive function in AD.…”
Section: Discussionmentioning
confidence: 99%